Potential Farm-Level Economic Impact of Incorporating Environmental Costs Into Nitrogen Decision Making: A Case Study in Canadian Corn Production - Banger, Kamaljit; Nasielski, Joshua; Janovicek, Ken; Sulik, John; Deen, Bill (Frontiers in Sustainable Food Systems, 2020)
Corn yield response to nitrogen (N) rates typically follows a flat plateau polynomial function with a relatively “flat” region on either side of the Economically Optimum N Rate (EONR). This flat region indicates that a wide range of N rates can approximate the maximum returns achieved at the EONR. To avoid yield penalties due to N stress, farmers tend to over- apply N which results in complex tension between farmers and other stakeholder groups. Using 10-years field data (2009–2018) from Elora, Ontario, we estimated the magnitude of cost to farmers if optimal N rate is based on both economic and environmental costs, and assessed whether incorporating environmental costs into optimum N rate increases profit variability. A cropping system model (DeNitrification and Decomposition model, DNDC) was calibrated and validated for corn yield and environmental N losses against five N rates (30, 58, 87, 145, and 218 kg N ha−1) during 2009–2018. Our results suggest that N rates could vary by 46–91 kg N ha−1 around the EONR without reducing profits substantially (<25 ha−1 of maximum profits) during 2009–2018. When environmental costs were accounted for, environmentally optimal N rate was reduced by 11–54 kg N ha−1 (7–31% of EONR) with maximum reductions in N rates occurred in an extremely dry (2012) year. With conservative estimates of the environmental costs of N loss, our study suggests that the environmental benefits accrued at environmentally optimal N rates are 2–4-folds' greater than the reduction in net farmer income. This indicates that the environmental returns to policies which compensate farmers for applying environmentally optimal N are large. Results of this study further suggest that farmers need to adjust N rates depending on the weather in a growing season.